Depression and anxiety in glaucoma patients using mono drug therapy vs polydrug therapy - Aaiza Tahir; Muhammad Waqas Ahmed; Summaya Khan; Omar Zafar; Muhammad Haroon Sarfraz; Muhammad Shahid Tarar (Journal of Rawalpindi Medical College)
Objective: To evaluate the frequency of depression, anxiety, and stress scores among glaucoma patients and assess factors attributing to severe scores.